Valorisation of sewage sludge through pyrolysis : product properties and immobilisation of heavy metals - Withanage Don Chanaka Udayanga (Nanyang Technological University, 2020)
Valorisation of the sewage sludge through pyrolysis is considered as a zero-waste technology as it converts the sewage sludge into tar, non-condensable gas and char which are potential resources for reclamation, leaving no waste residue to be disposed of. Pyrolysis conversion is a complex process due to the diverse composition of the sewage sludge. In addition, the presence of toxic compounds such as heavy metals in the sludge could lead to secondary contamination during pyrolysis. This study investigated the impacts of the sewage sludge characteristics and the pyrolysis conditions on the product properties and immobilisation of heavy metals in the derived char. Sewage sludge samples were collected from municipal (MS) and industrial (IS) water reclamation plants. Initially, humic acid (HA), CaO and kaolin were used to change the composition of MS to evaluate the effects of the organic and inorganic constitutes on pyrolysis product properties and heavy metals immobilisation. The presence of HA and kaolin influenced the non-condensable gas yield and composition. CaO in the sludge catalysed deoxygenation and ring opening reactions leading to an increment in aliphatic compounds in the organic phase of tar. The addition of HA and CaO to the sludge immobilised heavy metals in the derived char while kaolin appeared to be less effective. Next, sewage sludge samples with diverse characteristics (i.e. MS and IS) were used to systematically examine the impact of the decomposition of organic and the accumulation of inorganic on the properties of the char derived at typical pyrolysis temperature range (500-700°C). Both MS and IS showed similar thermal decomposition behaviour. Although the inorganic enrichment reduced the heating values of the derived char, the accumulation of some inorganic constituents improved their combustion reactivities. Pyrolysis of MS effectively immobilised heavy metals in the derived char. In contrast, IS-derived char at 700°C showed significantly high leaching potentials for Cu and Zn. This proved for the first time that high temperature pyrolysis could have detrimental effect for heavy metals immobilisation. Lastly, a comprehensive approach comprising conventional and advanced analytical characterisations was employed to reveal the mechanisms for heavy metals immobilisation during pyrolysis of IS. Results showed that reactions of halides with heavy metals at higher pyrolysis temperatures to form soluble metal compounds were the probable reasons for the increase in metal leaching potentials. Finally, recommendations and future research directions are proposed for the development of pyrolysis valorisation of sewage sludge that ensures the clean fuel production and heavy metals immobilisation.